Legal Concept of Oil Palm Plantation Supply Chain Partnership as an Effort to Increase Competitiveness for Business Actors - Astawa, I Ketut; Setiady, Tri; Iswari, Benny; Azizah, Faiqah Nur (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The study of the concept of partnership legal relationship patterns in the palm oil industry business world aims to explore the idea of partnership relationship patterns between farmers, processors, and suppliers in the oil palm plantation supply chain, as well as the role of each party in improving operational efficiency, sustainability, and competitiveness for business actors. Partnership legal relationship pattern theory emphasizes the importance of synergy and collaboration between various actors in the supply chain to achieve common goals. The purpose of this study is to examine the pattern of legal relationships in supply chain partnerships between the private sector and oil palm planters to enhance the competitiveness of business actors. Qualitative research methods with normative research types, descriptively analyzed to examine and explain the research objects to be researched through legal and conceptual approaches, with literature study data collection techniques to identify effective partnership models, such as partnerships between farmers and processing plants, which are based on agreements or contracts, as well as vertical partnerships that integrate various stages in the supply chain. Qualitative research methods with normative research types, descriptively analyzed to examine and explain the research objects to be researched through legal and conceptual approaches, with literature study data collection techniques to identify effective partnership models, such as partnerships between farmers and processing plants, which are based on agreements or contracts, as well as vertical partnerships that integrate various stages in the supply chain. The results of the study show that a good partnership can facilitate technology transfer, improve cultivation practices and strengthen the bargaining position of business actors and in general, the application of the concept of legal relationship patterns of oil palm plantation supply chain partnerships between private parties and private parties, oil palm planters in realizing the competitiveness of effective business actors in the supply chain can be a key strategy to increase the competitiveness of business actors and ensure Sustainability of the palm oil industry.